Comparative performance analysis of bitcoin cryptocurrency, stocks and gold as investments alternative - Tunnisa, Indah Fadila; Darmawan, Surya (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2023)
Based on data from the Indonesian Central Securities Depository (KSEI), more people are investing in the capital market due to easy access and education through technology. This study compares the performance of Bitcoin, stocks, and gold to help investors make informed choices. The sample consists of monthly closing prices for these three investments from January 1, 2018, to April 30, 2023, with a total of 192 data. Results show no significant return difference between Bitcoin, LQ45 stock, and UBS gold. However, there are significant differences in risk between these three investments. Performance calculations using Sharpe, Treynor, and Jensen methods also show significant differences. Based on the research, LQ45 stock is the best investment option for investors.